Artful Liars: Malingering on the Draw-A-Person Task - Carmody, Dennis P. (2011)
Malingering is a form of deception in which one fakes illness to earn (positive or negative) reinforcement. The purpose of the current research was to explore the ability of naïve participants to malinger distress on a clinical, projective measure (Draw-A-Person; DAP). In two experiments, individuals first drew figures of a man, woman, and self. Then, they imagined they were in a motor vehicle accident and drew the figures again as if they were falsely claiming distress from the accident. In Experiment 1, 65 undergraduates participated and in Experiment 2, 70 undergraduates and 40 high school students participated. The drawings were objectively scored using a standardized protocol and ‘honest’ and ‘malingered’ drawings were compared. In both Experiments, participants successfully malingered distress and did so by drawing more “primitively”, earning lower cognitive ability scores on their malingered drawings. Hence, objectively-scored DAP tasks are vulnerable to deliberate distortion by naïve individuals, though malingering detection may be possible in the future via cognitive skill scores. However, reliance on DAP tasks for diagnostic or forensic purposes currently seems questionable